Risk of small for gestational age babies in preterm delivery due to pregnancy-induced hypertension (Medical Journal of Indonesia, 2019)
BACKGROUND Pregnancy-induced hypertension (PIH) causes high maternal morbidity and mortality worldwide. This study aims to assess the impact of PIH on fetal growth according to gestational age in preterm deliveries. METHODS A prospective cohort study using secondary data was undertaken in Ende District, East Nusa Tenggara, Indonesia from September 2014 to August 2015. The t-test was performed to compare mean birth weight based on gestational week between normotensive and PIH women, continued by linear regression. The chi-square or Fisher exact test was also conducted to determine the probability of birthing small for the gestational age (SGA) and large for gestational age (LGA) babies between normotensive and PIH women. RESULTS A total of 1,673 deliveries were recorded in Ende Hospital over the 1-year study period, among which 182 cases involved preterm births. The PIH group had lower birth weight than normotensive women at each gestational age starting from 32–35 weeks (p=0.004; 95% CI 150.84–771.36). Normotensive women at gestational ages of 32 (p=0.05; 95% CI 0.01–0.83), 34 (p=0.37; 95% CI 0.01–4.12), and 36 (p=0.31; 95% CI 0.02– 2.95) weeks had a lower risk of birthing SGA babies than PIH women; LGA babies were recorded at gestational ages of 33 (p=1.00; 95% CI 0.07–37.73) and 35 (p=0.31; 95% CI 0.34–63.07) weeks. CONCLUSIONS Poor perfusion of the uteroplacental is one of the reasons behind intrauterine growth restriction, which results in SGA babies born to PIH women.